The extraordinary work of ordinary writing : Annie Ray's diary - Sinor, Jennifer, 1969- (University of Iowa Press, 2002)
Krutch's trenchant observations about life prospering in the hostile environment of Arizona's Sonoran Desert turn to weighty questions about humanity and the precariousness of our existence, putting lie to Western denials of mind in the "lower" forms of life: "Let us not say that this animal or even this plant has 'become adapted' to desert conditions. Let us say rather that they have all shown courage and ingenuity in making the best of the world as they found it.